Prediction of Stone Free Rate after Standard Percutaneous Nephrolithotomy using Stone Nephrolithometry Score in Nobel Medical College Teaching hospital – A Prospective Study - Shah, Ram Sagar; Thapa, Niraj; Shrestha, Jit Prakash; Koirala, Ashok; Mishra, Kartikesh; Jayshwal, Raju; Pokharel, Sinet; Pandey, Himal (Journal of Nobel Medical College, 2023)
Background: Amongst all the modalities of treatment for renal stones, percutaneous nephrolithotomy is preferred treatment for large volume renal stone disease. However, percutaneous nephrolithotomy is associated with the risk of postoperative complications and the problem of stone free status. So, a preoperative classification is necessary to grade the complexity of percutaneous nephrolithotomy and STONE (stone size, tract length, degree of obstruction, number of involved calices, and stone essence) nephrolithometry score is one of such kind. Materials and Methods: This is analytical study conducted at the Department of Urology and Kidney Transplant, Nobel Medical College and Teaching Hospital, Biratnagar, Nepal from January 2020 to July 2020. Total 115 patients were included in the study. These patients were subjected for percutaneous nephrolithotomy. Stone clearance was documented at the end of the surgery; on first postoperative day and at 4 weeks. Results: In our study the stone – free rate was 89.6%. 32 patients experienced complications (27.8%). The STONE (stone size, tract length, degree of obstruction, number of involved calices, and stone essence) score correlated with the postoperative stone – free status (P=0.001). The patients rendered stone free had statistically significant lower scores than the patients with residual stones (6.83 ± 1.83 vs 9.83 ± 2.08, P = 0.001). Conclusion: The STONE (stone size, tract length, degree of obstruction, number of involved calices, and stone essence) nephrolithometry score is a simple and easy tool to apply system for predicting complexity in stone clearance with percutaneous nephrolithotomy.